Proyecto Utopía: Colombian Initiative for Peace and the Defense of Rurality in Times of Post-Agreement - Alberio, Marco; Otálora-Buitrago, Adriana; Rendón Acevedo, Jaime Alberto; Vergara, Rubén (Canadian Journal of Nonprofit and Social Economy Research / Revue canadienne de recherche sur les OSBL et l’économie sociale)

(untitled) (SFU Canadian Institute for Studies in Publishing, 2025)
Rural Colombia faces persistent challenges stemming from historical neglect, conflict, and institutional fragility. Established in 2010 by Universidad de La Salle, Proyecto Utopía offers a territorially grounded model of social innovation that combines agronomic education with peacebuilding for youth from marginalized regions. In this article, we analyze Utopía’s philanthropic governance and cross-sectoral alliances. Using a mixed-methods approach, the study shows philanthropy as a strategic enabler of inclusive development. La Salle’s University Philanthropy Office has mobilized diverse actors through transparent, ethical, and participatory mechanisms, securing sustained support from over 736 donors. Utopía thus exemplifies how universities can mediate in post-conflict societies, linking grassroots initiatives with institutional frameworks. It offers a replicable model of socially embedded transformation aligned with sustainable development goals, and it is capable of rebuilding trust and fostering long-term rural resilience.